Towards a better understanding and analysis of controlled delay (CoDel) algorithm by using fluid modelling. Issue 1 (1st January 2019) - Patil, Sachin D.; Tahiliani, Mohit P.
Abstract : In this study, a modified fluid model is proposed to understand the design of controlled delay (CoDel) algorithm for active queue management (AQM) and analyse its sensitivity to parameter settings. CoDel significantly differs from other AQM algorithms because it operates at the head of the queue and adopts a deterministic packet drop strategy, unlike other algorithms that operate at the tail and adopt a probabilistic packet drop strategy. The correctness of the proposed fluid model is verified by comparing its results with those obtained from ns ‐2. Subsequently, using the model developed in this study, the authors analyse the performance of CoDel algorithm by changing its internal parameters and modifying its control law. They highlight the role of the internal parameters and control law on the ability of the CoDel algorithm to control queue delay. Their analysis shows that the CoDel algorithm is sensitive to its parameter settings and that its control law requires minor modifications to gain a better control over the queue delay.